Sustainable Improvement of Sanitation Access for The Community of Pangkep Regency: Challenges and Solutions - Nanang Rahmadani; Heri Tahir; Mustaring; Suarlin (Journal of Indonesian Scholars for Social Research, 2025)
Proper environmental sanitation is a crucial element in improving the quality of life and public health. In Pangkep Regency, although various efforts have been made to improve sanitation access, there are still significant challenges in terms of infrastructure, policy, and public awareness. This article aims to explore the challenges faced in enhancing sustainable sanitation access in Pangkep Regency and the solutions that can be applied to address these issues. This study employs a qualitative approach, gathering data through interviews with relevant stakeholders, field surveys, and literature review. The findings reveal that the main challenges in improving sanitation access in Pangkep Regency include limited regional budget, low public awareness of the importance of sanitation, and poor coordination between related institutions. Therefore, more robust and integrated policies, increased community participation, and the use of environmentally friendly technologies are needed to support sanitation sustainability. The proposed solutions include strengthening sanitation education programs, developing community-based sanitation infrastructure, and implementing efficient and eco-friendly waste management systems. It is expected that these solutions will accelerate the achievement of sustainable sanitation access in Pangkep Regency, which will ultimately have a positive impact on improving public health and community welfare.